Vloga povezovalcev v govorjenem diskurzu - Schlamberger Brezar, Mojca (Jezik in slovstvo, 2007)
The paper presents the concept of connectors from their basic definition to morpho-syntactic and functional definition. Their most common occurrences are analysed in a study of French and Slovene spoken discourse. A Slovene corpus of taped and transcribed negotiations and a French corpus of taped and transcribed talk shows les Polémiques were used for the analysis of spoken discourse.
Keywords: analiza diskurza; besedotvorje; Corpus linguistics; francoščina; French; korpusno jezikoslovje; primerjalne študije; skladnja; Slovene; slovenščina; syntax; word formation